The Role of Psychological Training in Human Development in The Development of Communication Qualities - Yuldasheva Happiness Mamasakhatovna (Zien Journals, 2022)
The emotional state of the participants in the educational process is a matter of serious concern today. In children, high anxiety, frequent general indifference or, conversely, increased nervousness or aggression are observed. Teachers also have minor nervousness, negative emotions, feelings of anxiety. All this leads to the need to find new means of psychological and pedagogical support to prevent negative emotions in the participants of the educational process today. One of the most widely used methods of psychological work by educational psychologists in recent years as a means of providing support is psychological training.
Keywords: participants; emotional; educational; emotions